Morphological and molecular characterization of two gastrointestinal parasites in Mustelus mustelus (Linnaeus, 1758) from Adriatic Sea. Issue 1 (1st January 2020) - Tedesco, P.; Gustinelli, A.; Caffara, M.; Marsella, A.; Toffan, A.; Fioravanti, M. L.
Abstract: Specimens of common smooth-hound, Mustelus mustelus, fished as bycatch in the Northwestern Adriatic Sea, were subjected to a complete parasitological examination. Parasites were processed for morphological and morphometric analyses aimed at identifying them to the species level. Parasite identity was confirmed through amplification and sequencing of 28S rDNA. The nematode Acanthocheilus rotundatus was recovered from the stomach and the proximal intestine, while the cestode Calliobothrium verticillatum was collected from the spiral valve. Our results confirm the occurrence of C. verticillatum in M. mustelus from the Mediterranean Sea and provide the first sequence data of A. rotundatus from the same area. Updated knowledge on the parasite fauna of M. mustelus from Adriatic Sea contributes to elucidating aspects of the ecology, biology and health status of elasmobranchs from the Mediterranean Sea, providing useful information for their proper management and conservation.